Sex hormones and competitive bidding - Burkhard C. Schipper (University of California, Department of Economics, 2012)
We correlate competitive bidding and profits in symmetric independent private value first-price auctions with salivary testosterone, estradiol, progesterone, and cortisol in more than 200 subjects. Females bid significantly higher and earn significantly lower profits than males. Moreover, females on hormonal contraceptives bid significantly higher and earn significantly lower profits than males. Bids are significantly positively correlated and profits are significantly negatively correlated with salivary progesterone when controlling for gender, the use of hormonal contraceptives, and demographics. This also applies to the female but not to the male subsamples separately. It especially applies to naturally cycling females not using hormonal contraceptives and to females in the luteal phase of their natural menstrual cycle when progesterone usually peaks. Surprisingly, we have null findings for testosterone as well as estradiol and cortisol. Controlling for risk aversion does not diminish our positive finding for progesterone. Yet, we show that our finding may be due to subjects with imprudent bidding behavior (i.e., weakly dominated bids).
Keywords: C72; C91; C92; D44; D81; D87; 330; Hormones; Testosterone; Estradiol; Progesterone; Cortisol; Steroids; Auctions; Gender; Competition; Aggression; Dominance; Risk-taking; Endocrinological economics